الزيادات الواردة في حق المؤمنين والكافرين في القرآن الكريم: دراسة موضوعية - الوادعي، بدرية بنت سعيد معيض (جامعة الإمام محمد بن سعود الإسلامية - الجمعية العلمية السعودية للقرآن الكريم وعلومه, 2020)
تناول البحث جمع ما وعد الله به المؤمنين من الزيادات المتتابعة والمترابطة، وما أوعد الله به الكفار من الزيادات المتوالية والمتعاقبة ودراستها دراسة موضوعية، ويهدف البحث إلى دراسة مواضع الزيادة لأهل الإيمان وأهل الكفر والعلاقة بينها، وقد سلكت في هذا البحث المنهج الاستقرائي الوصفي التحليلي. وكان من أهم نتائج البحث: • أن قوة الإيمان أو ضعفه تتحكم في بقية الزيادات المعطاة للمؤمنين قوة وضعفاً. • أن الكفر هو أصل كل زيادة للكافرين. وأما توصيات البحث فكان منها: 1- الاهتمام بدراسة موضوعات القرآن المتعلقة بالإيمان لطلب الزيادة. 2- حث طلاب العلم وخصوصاً حملة القرآن على الربط بين مواضع الزيادة الواردة في القرآن. 3- دراسة آيات الزيادة ومتعلقاتها دراسة بلاغية لاستخراج الأسرار البلاغية.
This research dealt with the collection of the successive and interrelated increases that Allah promised to the believers, and the successive and interrelated increases that Allah promised to the disbelievers and objectively studies the same. The research aims to study the positions of increase for the believers and the disbelievers and the relationship between them. In this research, I used the descriptive and analytical approach. The most important outcomes include: • The strength or weakness of faith controls the rest of increases given to believers with strength and weakness • The disbelief is the root of every increase for disbelievers. The recommendations of the research: 1. Paying attention to study the topics of the Qur’an related to faith in order to seek increase. 2. Urging scholars, especially the Qur’an learners, to link the places of increase mentioned in the Qur’an. 3. Study the verses of increase and its related topics rhetorical study to extract rhetorical secrets.
Keywords: القرآن الكريم -- تفسير القرآن -- حق المؤمنين -- حق الكافرين